Stem-end russeting of Golden Delicious apples : the possible role of Alternaria alternata - Rishworth, Hilton C.(Hilton Charles) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1989.